Yitzi and the giant menorah - Ungár, Richárd (Tundra Books, 2016)
When the people of Chelm receive a giant menorah as a gift from the mayor of Lublin, the villagers try to come up with a fitting way to thank the mayor, but it isn't until the last night of Hanukkah that young Yitzi comes up with the right idea.